Carbon footprint, economic benefits and sustainable fishing: Lessons for the future from the Western Mediterranean - Muñoz, María; Reul, Andreas; Guijarro, Beatriz; Hidalgo, Manuel (Elsevier, 2023)
Ensuring an economically viable, sustainable and low CO2 emission extractive fishery is critical in order to achieve sustainable development goals and the climate change commitments. This challenge is even more relevant in the most overexploited region of the world: The Mediterranean Sea. Here, we use the socio-ecological system of the Spanish Mediterranean commercial fisheries (Northern Alboran Sea, Northern Spain and the Balearic Islands) to develop an integrative impact assessment, including detailed socio-economic, ecosystem indices of the trophic structure of extractive fishery and CO2 emission analyses combining different gear, vessel size classes as well as a wide range estimation of carbon release from the seafloor by bottom trawling. Northern Alboran Sea preferentially requires reduction in purse seine fishery while in Northern Spain bottom trawling should be reduced first to reach sustainable exploitation. Fuel CO2 footprint of purse seine and bottom trawling are among the lowest footprints of animal protein production, but considering sweeping released CO2 from the seafloor the bottom trawling footprint becomes the animal protein production with the highest footprint. Moreover, the lowest bottom released CO2 estimation overrides 2.7–10 times the CO2 buried in the seafloor through the biological pump in trawled areas potentially turning the continental shelf from a CO2 sink to a CO2 source. Net profit per fuel derived CO2 emission for all fleets is lower than 1€ kgCO2−1, being lowest for large bottom trawler (0.025 € kgCO2−1). Thus, urgent mitigation and adaptation measures are necessary to obtain sustainable fishery in terms of net profit, sustainable seafood extraction and CO2 emission reduction. Our study provides scientific bases to develop these measures such as the restriction of harmful fishing gear in carbon rich river influenced areas, reduction of bottom contact of the fishing gear, favouring purse seine fishery and smaller bottom trawlers.
Keywords: Ecología; Geología; Bottom carbon release,Trophic level, Primary production, required CO2, footprint, Fuel consumption; Bottom carbon release; Trophic level; Primary production; Required CO2; Footprint; Fuel consumption